Moisture-solid transfer during osmotic dehydration of banana(musa sapietum) varieties (2003)
"Moisture solids transfer during the osomotic dehydration of three banana (musa sapietum) varieties was investigated. Cavendish, Omini-red and Cooking banana were transversely sliced into 10, 15 and 20mm thicknesses. Sample of each thickness were immersed in 52, 60 and 68 B sucrose solutions. A fruit: solution ratio of 1:20(w/w) was maintained. The fruit-solution moistures were kept at 27, 34, and 40 C for 12 hours. Samples were evaluated gravimetrically at 2 hours interval. Moisture and total solids contents were determined and expressed as g water/g dry matter (DM) and g solids/g initial mass respectively. Moisture contents on dry basis of the banana slices were found to decrease with increased immersion time, solution concentration and temperature. However, moisture contents decreased with decreased slice thickness. Total solids contents increased with thickness. Omini red cultivar had the lowest moisture content and the highest total solids contents at the end of 12 hours of osmotic treatment. Complex polynomial equation showing the relationship with moisture and total solids contents with immersion time showed high correlation (R2=0.9919-1.000) "